Influence of cigarette smoke combined with different toothpastes on enamel erosion - Laura Nobre Ferraz; Núbia Inocêncya Pavesi Pini; Gláucia Maria Bovi Ambrosano; Flávio Henrique Baggio Aguiar; Débora Alves Nunes Leite Lima
Abstract: This in vitro study aimed to evaluate the effect of different toothpastes on dental enamel subjected to an erosive cycle with and without exposure to cigarette smoke. Bovine enamel specimens were randomly allocated into 12 groups (n = 12). For the in vitro simulation of smoking, half the groups underwent an exposure cycle of 20 cigarettes per day for 5 days. Subsequently, all groups were subjected to a 5-day erosion cycle intercalating demineralization (1 min; 1% citric acid; pH = 3.5) and treatment with toothpaste slurries (2 min) of NaF, SnF2, F/Sn/Chitosan, F/CaSiO3/Na3PO4, and F/bioactive glass. The control group was immersed in distilled water. Surface microhardness (SMH) was measured initially, after exposure to smoke, and after the erosive cycle, and %SMH was calculated. At the end of the experimental cycle, surface roughness, profilometry, and atomic force microscopy (AFM) were performed. SMH increased after exposure to cigarette smoke (p < 0.05). After the erosive cycle, there were no differences between the presence and absence of cigarette smoke exposure in SMH and roughness (p > 0.05). Besides increasing enamel SMH, cigarette smoke did not prevent enamel loss after the erosion cycle (p < 0.05). In profilometry, roughness and surface loss had the lowest values in the groups treated with SnF2 and F/Sn/Chitosan (p < 0.05). AFM showed lower mineral loss with F/CaSiO3/Na3PO4 and F/Sn/Chitosan. For all groups, except F/CaSiO3/Na3PO4, cigarette smoke resulted in higher enamel wear. F/Sn/Chitosan showed the best results against erosion.